Інформаційні технології в проєктуванні ІС - Бондаренко, І. М.; Карнаушенко, В. П.; Грицунов, О. В. (ХНУРЕ, 2025)
Information Technology has attracted the attention of developers with its potential in developing integrated circuits by simplifying the design process, increasing productivity, and accelerating the time to market. By automating routine tasks and optimizing complex design decisions, Artificial Intelligence can help developers achieve greater efficiency than before. However, despite the numerous advantages of modern solutions, there are also significant limitations, especially in critical cases involving real-world tasks related to coordinating external data sources. Therefore, it is necessary to consider both the benefits of artificial intelligence in designing integrated circuits, including automation, optimization, and error reduction, and the problems that limit its effectiveness in specific complex applications.
Keywords: проєктуванняі ІС